Expand grid decarbonization by associating more technology investment with voluntary corporate procurement - Kittner, Noah (Frontiers in Sustainable Energy Policy, 2025)
Corporate greenhouse gas emission reporting standards are being revised. There is a new opportunity to include investments in much-needed technologies such as energy storage, electricity transmission upgrades, and generation as part of a new accounting method. Revising the protocol could catalyze private investment in critical technologies that have been excluded from these systems.